Digital processing of geoelectrics data applying the Ridge Regression in the Parish Olegario Villalobos of the Municipality Maracaibo, Zulia State - Márquez, Wilmer; Cardozo, María; Villasmil, Gerson (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This investigation, is based on the Ridge Regression method for the processing digital of geoelectrics data, applied in 1970 by Marquardt, Hoerl and Kennard, and in 1973 by Joseph Robert Inman, which involve robust statistical parameters to obtain better results of apparent resistivity values and thickness for lineally dependent systems, using, the Vertical Electric Sound Method under the Schlumberger electrodic configuration in the Parish Olegario Villalobos of the Municipality Maracaibo. This geoelectric information is processed with the Ghosh Method, applying lineal models that generate curves of apparent resistivity for optimizing the obtained variables with the Ridge Regression method, the half error and the residual variance, among other indicate the residual deviation, the estimate range and the noise level on the data, the last one is defined in 3% as a, product of the relationship between the half percentage error and the standard deviation which define reliable parameters in the interpretation phase of the is geoelectrics these profile indicate the presence of fresh water aquifer, with a top of 30 m, a base of 80mprofile and a flow of 2 L/seg, in the sector Las Mercedes school.